High-resolution notch filters and diplexers based on SU-8 inverted rib waveguides - Malheiros-Silveira, Gilliard N. [UNESP]; Finardi, Celio A.; Bürger, Talita S.; Van Etten, Eliana A.M.A.; Da Silva, Ricardo C.G.; Coelho, Artur V.P.; Daltrini, André M.; Panepucci, Roberto R. (Optica Publishing Group, 2019)
We performed an end-to-end process, ranging from design, fabrication, and characterization of integrated polymeric optical devices under a mass production technology. Inverted rib waveguides formed by SU-8 photoresist deposited on top of full wafers, with trenches in silica, were used as a platform to implement such optical devices. Narrowband spectral filters based on microracetrack resonators and diplexers based on directional couplers, both with high extinction ratios, are demonstrated. Full wafers of those devices were processed in a complementary metal-oxide-semiconductor foundry’s 150 mm-facility. We believe the results are promising for applications ranging from telecommunication components to sensing devices.